W kręgu socjologii wychowania Floriana Znanieckiego - Leśniak-Moczuk, Krystyna (Rocznik Pedagogiczny, 2021)
The aim of this article is to recall the theory of the sociology of education created almost a century ago by the classic of Polish sociology, Florian Znaniecki, in order to show the topicality of his concept in the face of the symptoms of the crisis of the educational system. The article presents the biographical context and scientific achievements of the creator of the sociology of education. The relations between the disciplines of educational sociology, general sociology and pedagogy were explained. The goals and components of the upbringing process and the system of sociology of upbringing by Florian Znaniecki were outlined. Attention was also paid to the educational environ- ment defined by Florian Znaniecki and the upbringing process was characterized as a preparation for fulfilling the social roles. The theses postulated by the creator of the sociology of education were related to the contemporary educational environment.